Characterizing Heart Failure Across the Spectrum of the Preserved Ejection Fraction: Does Heart Failure With Supranormal Ejection Fraction Exist? Data From the Swedish Heart Failure Registry - Laura Landucci; Ulrika Ljung Faxén; Lina Benson; Giuseppe M. C. Rosano; Ulf Dahlström; Lars H. Lund; Gianluigi Savarese (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sparce data suggest higher mortality in heart failure (HF) with left ventricular ejection fraction (EF) >65% to 70%. We characterized EF distribution, characteristics, and outcomes in patients with HF and EF ≥50%. Methods and Results There were 5576 patients enrolled in the Swedish HF registry between 2017 and 2021 and included in the study; 21% had EF ≥60%, 5% EF ≥65%, and 1.5% EF ≥70%. Patient characteristics independently associated with EF ≥60% were assessed by multivariable logistic regression and were identified as being a diagnosis of hypertrophic cardiomyopathy, worse New York Heart Association class, hypertension, and valvular disease, whereas use of medications and devices also recommended for HF with reduced EF, male sex, history of ischemic heart disease, peripheral artery disease, and chronic obstructive pulmonary disease were associated with an EF of 50% to 59%. Outcomes (all‐cause, cardiovascular, and noncardiovascular death; all‐cause and HF hospitalizations) were assessed by univariable and multivariable Cox regressions with EF modeled as a spline. The risk of all‐cause and noncardiovascular mortality and first all‐cause hospitalization was higher with EF values >55% in crude but not adjusted analyses. Conclusions Among patients with HF with preserved EF, 21% had EF ≥60%. A higher EF was characterized by more severe symptoms, hypertrophic cardiomyopathy, hypertension, female sex, and valvular disease. Crude higher but not adjusted risk of all‐cause and noncardiovascular mortality and of all‐cause hospitalization was observed with EF values >55%, suggesting that prognostically impactful conditions were more prevalent in the upper bound of the EF spectrum.